Effects of ethanolic extracts of Garcinia kola seeds on growth and haematology of catfish (Clarias gariepinus) broodstock - A. A. Dada; M. Ikuerowo (Advances in Aquaculture and Fisheries Management, 2017)
A 56 day study was undertaken to evaluate the effects of dietary ethanolic extracts of Garcinia kola (Bitter kola) in African catfish, Clarias gariepinus broodstock on growth performance and basic haematological indices. Catfish broodstock (mean weight, 245.20 – 255.00 g) were randomly distributed into concrete tanks (2 x 2 x 1.2 m) at 10 fish/tank in triplicate treatments. 5 diets (40% crude protein) containing varying levels of ethanolic extracts of G. kola at 0, 0.25, 0.5, 1.0 and 2.0 g/kg diets were prepared (representing diets 1 - 5, respectively) and fed to mixed sex C. gariepinus brodstock twice daily (0900 - 0930 h and 1700 - 1730 h) for 56 days to evaluate the effects on growth parameters, feed utilization and haematological parameters. There were significant variations (p > 0.05) in the growth parameters and food conversion ratio. Fish fed 1.0 g/kg diets of ethanolic extracts of G. kola had the best weight gain than fish fed ethanolic extracts of G. kola seeds of 0, 0.25, 0.5 and 2.0 g/kg feed with significant differences (P < 0.05) among the treatments. Similarly the specific growth rate (SGR) was higher in fish fed 1.0 g/kg diet of ethanolic extracts of G. kola seeds with significant different found between the treatments, the weight gain increased as the inclusion levels of ethanolic extracts of G. kola seeds in the diets increased up to 1.0 g/kg diets and decreased as the inclusion levels increased up to 2.0 g/kg feed. This support the probiotic effects of G kola seeds as growth promoter, haematological parameters such as pack cell volume (PCV), haemoglobin concentration (Hb) and red blood cells (RBC) for fish fed on diets D2 to D5 were not significantly different from that of the control (D1). However there was a significant (P < 0.05) proliferation of the white blood cells (WBC) in this study. This probably explains the antimicrobial effect of ethanolic extracts of G. kola seeds in view of the major role that the white blood cells assume in the immunity defence mechanism of the body in both man and animals.